Antibody and cellular therapies for treatment of covid-19: a living systematic review and network meta-analysis. (23rd September 2021) - Siemieniuk, Reed AC; Bartoszko, Jessica J; Díaz Martinez, Juan Pablo; Kum, Elena; Qasim, Anila; Zeraatkar, Dena; Izcovich, Ariel; Mangala, Sophia; Ge, Long; Han, Mi Ah; Agoritsas, Thomas; Arnold, Donald; et al.
Abstract: Objective: To evaluate the efficacy and safety of antiviral antibody therapies and blood products for the treatment of novel coronavirus disease 2019 (covid-19). Design: Living systematic review and network meta-analysis, with pairwise meta-analysis for outcomes with insufficient data. Data sources: WHO covid-19 database, a comprehensive multilingual source of global covid-19 literature, and six Chinese databases (up to 21 July 2021). Study selection: Trials randomising people with suspected, probable, or confirmed covid-19 to antiviral antibody therapies, blood products, or standard care or placebo. Paired reviewers determined eligibility of trials independently and in duplicate. Methods: After duplicate data abstraction, we performed random effects bayesian meta-analysis, including network meta-analysis for outcomes with sufficient data. We assessed risk of bias using a modification of the Cochrane risk of bias 2.0 tool. The certainty of the evidence was assessed using the grading of recommendations assessment, development, and evaluation (GRADE) approach. We meta-analysed interventions with ≥100 patients randomised or ≥20 events per treatment arm. Results: As of 21 July 2021, we identified 47 trials evaluating convalescent plasma (21 trials), intravenous immunoglobulin (IVIg) (5 trials), umbilical cord mesenchymal stem cells (5 trials), bamlanivimab (4 trials), casirivimab-imdevimab (4 trials), bamlanivimab-etesevimab (2 trials), control plasma (2 trials), peripheral blood non-haematopoietic enriched stem cells (2 trials), sotrovimab (1 trial), anti-SARS-CoV-2 IVIg (1 trial), therapeutic plasma exchange (1 trial), XAV-19 polyclonal antibody (1 trial), CT-P59 monoclonal antibody (1 trial) and INM005 polyclonal antibody (1 trial) for the treatment of covid-19. Patients with non-severe disease randomised to antiviral monoclonal antibodies had lower risk of hospitalisation than those who received placebo: casirivimab-imdevimab (odds ratio (OR) 0.29 (95% CI 0.17 to 0.47); risk difference (RD) −4.2%; moderate certainty), bamlanivimab (OR 0.24 (0.06 to 0.86); RD −4.1%; low certainty), bamlanivimab-etesevimab (OR 0.31 (0.11 to 0.81); RD −3.8%; low certainty), and sotrovimab (OR 0.17 (0.04 to 0.57); RD −4.8%; low certainty). They did not have an important impact on any other outcome. There was no notable difference between monoclonal antibodies. No other intervention had any meaningful effect on any outcome in patients with non-severe covid-19. No intervention, including antiviral antibodies, had an important impact on any outcome in patients with severe or critical covid-19, except casirivimab-imdevimab, which may reduce mortality in patients who are seronegative. Conclusion: In patients with non-severe covid-19, casirivimab-imdevimab probably reduces hospitalisation; bamlanivimab-etesevimab, bamlanivimab, and sotrovimab may reduce hospitalisation. Convalescent plasma, IVIg, and other antibody and cellular interventions may not confer any meaningful benefit. Systematic review registration: This review was not registered. The protocol established a priori is included as a data supplement. Funding: This study was supported by the Canadian Institutes of Health Research (grant CIHR- IRSC:0579001321). Readers' note: This article is a living systematic review that will be updated to reflect emerging evidence. Interim updates and additional study data will be posted on our website (www.covid19lnma.com ).